FAKTOR FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN DALAM KEPUTUSAN PEMBELIAN HP OPPO DI METEOR CELL KECAMATAN MARISA KABUPATEN POHUWATO - Lely Afiati (AkMen JURNAL ILMIAH, 2017)
Consumer behavior is a process through which an individual / organization in searching, buying, using, evaluating, and disposing of products or services after being used for kebutuhanya. According to Philip Kotler (1996: 144) mengemumakan that factors that affect yann consumer behavior are: 1. Factors Culture 2. Social Factors 3. Personal Factors 3. Psychological Factors. The sample of the research is the buyer who has made a purchase of HP OPPO in Meteor Cell Sub District Marisa Pohuwato District with 30 buyers. Data were analyzed by using SPSS program version 16. The test result is: From the research result can be explained that consumer behavior variable simultaneously have positive and significant effect to the variable of Purchase Decision at the level of significant test of alpha (0,00) equal to 324,885 (3,24% ); Cultural variables (X1) have a positive effect on the Purchase Decision variable by 0.20 (20%); Social variables (X2) have a positive effect on the decision variable Pembeliansebesar 0.03 (3%); Personal variable X3 positively affects the Purchase Decision variable by 0.31 (31%); Psychology variable X4 has a positive effect on Purchase Decision variable of 0.983 (9.83%).